Uso de PET SCAN en el estudio de la fiebre de origen desconocido, en una IPS de alta complejidad en Bogotá DC, Colombia (2025)
Fever of unknown origin (FUO) remains a frequent diagnostic challenge in clinical practice, particularly in high-complexity settings. Despite advances in diagnostic methodologies, a significant proportion of patients remain without a clear etiological diagnosis, delaying timely therapeutic interventions. The 18F-FDG-PET/CT has emerged as a valuable tool for identifying infectious, inflammatory, or neoplastic foci in these cases. However, its performance in the Colombian population has not been widely documented. A retrospective descriptive study was conducted to assess the utility of 18F-FDG-PET/CT in the diagnostic approach to patients with FUO hospitalized at a tertiary care institution in Bogotá, Colombia, between 2019 and 2023. A total of 38 patients were included, and clinical, laboratory, and imaging data were collected. Descriptive statistical analysis was performed, including frequencies, percentages, medians, and interquartile ranges. In 84.2% of cases, 18F-FDG-PET/CT contributed to guiding the diagnosis or identifying a probable underlying cause. In 28 patients (73.68%), the PET/CT findings were concordant with other diagnostic tests and the final diagnosis. In 16 cases (42.10%), PET/CT findings led to changes in clinical management or prompted additional targeted investigations. In conclusion, 18F-FDG-PET/CT proved to be a highly useful diagnostic tool in the evaluation of patients with FUO, particularly in those with inconclusive initial workups.